Prognostication in the medieval world a handbook - Heiduk, Matthias; Herbers, Klaus 1951-; Lehner, Hans Christian 1982- (De Gruyter Reference Ser., 2020)
Intro -- Contents -- In gratiam et in memoriam -- Volume 1 -- Introduction -- Part I: Introductory Surveys -- Divination in Antiquity -- Early Medieval Perspectives on Pre-Christian Traditions in the Celtic World -- Pagan Traditions of Prognostication in the Germanic Languages -- Prognostication in Pagan Beliefs among Slavs in the Middle Ages -- Prognostication in the Medieval Western Christian World -- Prognostication in the Medieval Eastern Christian World -- Prognostication in Medieval Jewish Culture -- Medieval Traditions of Prognostication in the Islamic World -- Prognostication in Early Modern Times - Outlook -- Part II: Traditions and Practices of Prognostication in the Middle Ages -- Eschatology and Millenarism -- Traditions and Expectations in the Medieval Western Christian World -- Traditions and Expectations in the Medieval Eastern Christian World -- Jewish Traditions and Expectations in the Medieval World -- Traditions and Expectations in the Medieval Islamic World -- Prophecy and Visions -- Traditions and Practices in the Medieval Western Christian World -- Jewish Traditions and Practices in the Medieval World -- Traditions and Practices in the Medieval Islamic World -- Dream Interpretation -- Traditions and Practices in the Medieval Western Christian World -- Traditions and Practices in the Medieval Eastern Christian World -- Jewish Traditions and Practices in the Medieval World -- Traditions and Practices in the Medieval Islamic World -- Mantic Arts -- Traditions and Practices in the Medieval Western Christian World -- Traditions and Practices in the Medieval Eastern Christian World -- Jewish Traditions and Practices in the Medieval World -- Traditions and Practices in the Medieval Islamic World -- Astral Sciences -- Traditions and Practices in the Medieval Western Christian World.